PENGARUH KUALITAS PELAYANAN, PROMOSI DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (PENELITIAN PADA “MEKAR” SWALAYAN-KOPERASI KARYAWAN “MEKAR” PT. GUDANG GARAM TBK KEDIRI) - Khusnul Chotimah; Sri Wahyuni Mega Hastuti; Sumarji Sumarji (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Employee cooperatives are cooperatives located in a company and members of the cooperative are employees of the company. the cooperative is given the opportunity to set up its own business unit. Over time the business unit continued to grow rapidly and the business unit changed its name to